2016
DOI: 10.5433/1679-0359.2016v37n2p969
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of corn by forage cactus in the diets of lactating goats

Abstract: The objective of this trial was to evaluate the effect of the partial replacement of corn by forage cactus (Nopalea cochenillifera Salm Dyck) in the diets of lactating goats on the nutrient intake, milk production and composition and ingestive behavior. Five crossbreed Saanen x Pardo Alpina goats with body weights of 47 ± 3.3 kg were used in the study. The design was 5x5 Latin square design, in which the treatments were as follows: 20, 25, 30, 35 and 40% of girl cactus included in the diet as a partial replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Bispo et al [7], while investigating the feed of sheep, observed that water intake decreased from 3.25 L/d to 0.44 L/d when forage cactus pear was used as feed from 0 to 560 g/Kg of dry matter (DM), substituting for elephant grass. Forage cactus pear is an excellent alternative for increasing water availability through feed [8][9][10] and is widely used as a feed ingredient in sheep diets in semiarid and arid regions because of its good adaptability to soil and weather conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Bispo et al [7], while investigating the feed of sheep, observed that water intake decreased from 3.25 L/d to 0.44 L/d when forage cactus pear was used as feed from 0 to 560 g/Kg of dry matter (DM), substituting for elephant grass. Forage cactus pear is an excellent alternative for increasing water availability through feed [8][9][10] and is widely used as a feed ingredient in sheep diets in semiarid and arid regions because of its good adaptability to soil and weather conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The results of milk production in this work, regarding the research presented by Pereira et al (2021), Ramos et al (2020), Sousa et al (2018), Lopes et al (2017), andGoveia et al (2016) highlight the possibility that the producer has, in certain semi-arid areas of northeastern Brazil, two genotypes of cactus cladodes resistant to carmine scale, with a forage/concentrate ratio of 80:20, and a reduction of water via food above 78% in all diets, contributing to less dependence on the concentrate feed market.…”
Section: Resultsmentioning
confidence: 51%
“…In another research with Anglo Nubiana goats (43 kg), Pereira et al (2021) used 40% buffel hay and replaced 100% of corn (Nopalea cochenillifera), reported a mean daily milk production value of 997g. With Saanen x Pardo Alpina goats (47 kg), Goveia et al (2016) using 45% gliricidia hay (Gliricidia sepium (Jacq) Walp) and replacement of up to 72% ground corn for Miúda cactus cladodes, reported an average daily milk production value of 1.18 kg. However, several aspects must be taken into account for these differences: size and age of goats, level of production, quantity, and quality of forage in the diets, among others.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is adapted to semiarid regions, the reduced fiber and crude protein concentrations of forage cactus leads to a need to balance the diet of livestock. Thus, one of the alternatives to balance the diet of livestock with proteins and fibers when feeding cactus is intercropping cactus with tree legumes [1]. In addition, tree legumes can enhance N input in the agroecosystem via biological N2 fixation.…”
Section: Introductionmentioning
confidence: 99%